2020
DOI: 10.7759/cureus.7105
|View full text |Cite
|
Sign up to set email alerts
|

Voxelotor: A Ray of Hope for Sickle Disease

Abstract: Sickle cell disease is one challenging blood disorder, affecting around 100,000 people in the United States alone. None of the currently approved drugs can modify the underlying pathology of the disease. Voxelotor, first of its kind, is an orally administered drug that can alter the underlying disease pathology (by increasing the affinity between Hb and oxygen) and inhibit sickling of red blood cells. Several clinical trials and case series have documented the benefits and safety of voxelotor therapy in sickle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Several clinical trials have reported its benefits. 73 Crizanlizumab is a new, FDA-approved drug for the prevention of VOC. It is a humanized IgG2 kappa monoclonal antibody that binds to P-selectin and blocks interactions with its ligands including P-selectin glycoprotein ligand 1.…”
Section: Hydroxyurea and New Therapeutic Approachesmentioning
confidence: 99%
“…Several clinical trials have reported its benefits. 73 Crizanlizumab is a new, FDA-approved drug for the prevention of VOC. It is a humanized IgG2 kappa monoclonal antibody that binds to P-selectin and blocks interactions with its ligands including P-selectin glycoprotein ligand 1.…”
Section: Hydroxyurea and New Therapeutic Approachesmentioning
confidence: 99%
“…Acute and chronic manifestations increase with age and these complications lead to early mortality. Approximately 100 000 individuals are affected by SCA within the United States alone and the condition dramatically decreases life expectancy by about 30 years 4 …”
Section: Figurementioning
confidence: 99%
“…Approximately 100 000 individuals are affected by SCA within the United States alone and the condition dramatically decreases life expectancy by about 30 years. 4 Voxelotor (GBT440) is a first-in-class, oral, once-daily drug (Global Blood Product, San Francisco, CA) that binds to the α-chain of haemoglobin S (HbS), which is known to interrupt HbS polymerisation. [5][6][7] This study aimed to conduct a meta-analysis of the efficacy of voxelotor 900 mg in patients with SCA.…”
mentioning
confidence: 99%
“…There is a great expectation regarding the use of voxelotor as “it consists the first of its kind,” meaning that it could potentially alter the underlying SCD pathology. After a series of clinical trials (NCT02285088, NCT03041909), this drug has shown great benefits by increasing the affinity between Hb and oxygen resulting in the inhibition of drepanocytosis of the RBCs and therefore, to a significant improvement in patients’ quality of life [ 42 , 43 ]. Subsequently, in phase 3 clinical trial called GBT_HOPE (NCT03036813), voxelotor established efficacy and safety even with concomitant administration of placebo (hydroxyurea), in patients with SCD ( N = 274).…”
Section: Introductionmentioning
confidence: 99%